A hydroxypropyl methylcellulose modified additive composition specifically for gypsum-based self-leveling mortar and a preparation method thereof
By using lithium sulfate and sodium gluconate modified hydroxypropyl methylcellulose additives in gypsum-based self-leveling mortar, the problems of insufficient ease, suspension and initial strength during the construction process are solved, and the high suspension of the mortar is achieved , stability and strength enhancement ensure the convenience of construction and high strength and flatness after hardening.
Patent Information
- Application Number
- CN202310353611.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-31
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-03-31
AI Technical Summary
The prior art has shortcomings in improving the ease, suspension and initial strength of gypsum-based self-leveling mortar, resulting in inconvenience in the construction process and ultimately improving the stable performance without ignoring the impact of the construction process.
Using hydroxypropyl methylcellulose modified additive compositions, including lithium sulfate and sodium gluconate, improve suspension and stability through charge repulsion and adjust solidification time through retarding to ensure that the mortar does not settle or settle during hardening. Layered and no water secretion can improve compressive and flexural strength.
It significantly improves the suspension, stability and hardening strength of gypsum-based self-leveling mortar, ensures easy construction, flat surface, and improves compressive and flexural strength, avoids settlement, stratification and water leakage, and improves construction efficiency and Product quality.
Smart Images

Figure CN116444194B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a hydroxypropyl methylcellulose modified additive composition specially used for gypsum-based self-leveling mortar and a preparation method thereof, belonging to the technical field of hydroxypropyl methylcellulose. Background Art
[0002] Gypsum-based self-leveling mortar is a building material made by mixing gypsum, aggregate and various building additives. It is used to repair floor defects, usually indoor floors. The corresponding product standard formulated in my country is JC / T1023-2021 "Gypsum-based self-leveling mortar". This material is easy to use and has the characteristics of self-leveling. It can naturally fill depressions or uneven places on the ground. It can also dry in a shorter time, helping to quickly complete the floor repair work.
[0003] Hydroxypropyl methylcellulose (HPMC) is a common building material additive and is also widely used in other fields. It is a compound obtained by chemical treatment of natural cellulose and has multiple functions and characteristics. In building materials, HPMC can be used to increase viscosity, improve fluidity, improve adhesion and delay setting time. Various types of hydroxypropyl methylcellulose are used in building materials such as ordinary mortar, thermal insulation mortar, bonding mortar, self-leveling mortar, interior and exterior wall putty, and anti-cracking mortar. After adding hydroxypropyl methylcellulose to mortar, it can make the mortar have good water retention, and can keep sufficient water in the system for a long time to participate in the hydration reaction of cementitious materials such as cement and gypsum. It can also make the mortar have good workability and facilitate its coating on walls or floors. In self-leveling mortar, it plays a role in slurry suspension, so that the materials in the system will not segregate, ensuring the construction quality of self-leveling mortar.
[0004] With the development of domestic economy, people have continuously put forward new requirements for building materials, and the requirements of relevant national standards and industry standards are getting higher and higher. Traditional HPMC can no longer meet the market requirements. It is an important means to improve the performance of building mortar by continuously optimizing the performance of HPMC. The current mainstream technical means is to modify HPMC.
[0005] As a new type of building functional mortar, self-leveling mortar has different performance requirements for hydroxypropyl methylcellulose from traditional building mortar. Since self-leveling mortar has good fluidity, the components with higher density can easily settle to the bottom layer, so the suspension requirements for hydroxypropyl methylcellulose are relatively high. In addition, due to the construction period, it is required to be convenient for construction, and it must solidify as soon as possible after the construction is completed, so that subsequent construction can be carried out as soon as possible. However, the existing technical means are limited to improving the final stability of self-leveling mortar, while ignoring the workability, suspension and initial strength of self-leveling mortar, which brings inconvenience to the construction process.
[0006] For example, the Chinese invention patent with application publication number CN 114835461 A discloses a high-strength gypsum-based self-leveling mortar. It includes building gypsum, water, cement, silica fume, fly ash, sand aggregate, water retaining agent, retarder, water reducer, defoaming agent and rubber powder, and the water retaining agent is hydroxypropyl methylcellulose. This patent scheme focuses on the performance of the self-leveling mortar after final stabilization, such as 24h compressive strength, 28d absolute dry compressive strength, dimensional change rate, crack resistance, etc., while ignoring factors that have a greater impact on the construction process, such as workability and suspension, and its initial strength is not very ideal. Therefore, it is of great significance to provide a self-leveling mortar with good workability, good suspension, high compressive strength and high flexural strength. Summary of the invention
[0007] The present invention aims to solve the above problems, thereby providing a hydroxypropyl methylcellulose modified additive composition specifically for gypsum-based self-leveling mortar. The hydroxypropyl methylcellulose modified additive composition of the present invention can significantly improve the suspension and stability of the gypsum-based self-leveling mortar, without sedimentation, stratification or water seepage; and can also significantly improve the strength of the gypsum-based self-leveling mortar.
[0008] The technical solution of the present invention to solve the above problems is as follows:
[0009] A hydroxypropyl methylcellulose modified additive composition specially used for gypsum-based self-leveling mortar, comprising the following components in parts by weight:
[0010] Hydroxypropyl methylcellulose 100,
[0011] Lithium sulfate 0.06~0.25,
[0012] Sodium gluconate 0.12~0.62.
[0013] The invention modifies hypromellose by using a modifier selected through a large number of experiments, thereby preparing an additive composition mainly containing hypromellose for gypsum self-leveling mortar. After being applied to gypsum-based self-leveling mortar, the additive composition has a significant improvement effect on the workability, compression resistance, flexural strength, suspension and other properties of the self-leveling mortar.
[0014] In the above technical scheme of the present invention, the charge repulsion effect of the electrolyte lithium sulfate is used to improve the suspension and stability of the material inside the gypsum-based self-leveling mortar system, so that the mortar does not settle during the hardening process, and the compressive and flexural strengths are significantly improved after hardening.
[0015] In the above technical solution of the present invention, sodium gluconate has a certain retarding effect. The present invention adjusts the setting time by controlling the dosage of sodium gluconate, so that the actual setting time of the mortar matches the optimal theoretical time required for the hydration of the semi-hydrated gypsum, thereby avoiding the occurrence of bleeding, and at the same time further improving the strength of the gypsum-based self-leveling mortar after hardening. This is because, under the action of sodium gluconate and lithium sulfate, the hydration process of the semi-hydrated gypsum is controlled to proceed more evenly, and the internal crystal structure is evenly arranged, so that the internal defects of the gypsum material are greatly reduced, thereby significantly improving the structural strength, which is macroscopically manifested as improved compressive and flexural strengths.
[0016] Therefore, after adopting the above technical solution, the gypsum-based self-leveling mortar does not settle during the hardening process, the hardened mortar does not stratify, the surface is smooth and flat, and the compressive and flexural strengths are improved.
[0017] As a preferred embodiment of the above technical solution, the mass parts of each component are as follows: 100 parts of hypromellose, 0.10-0.15 parts of lithium sulfate, and 0.34-0.38 parts of sodium gluconate.
[0018] As a preferred embodiment of the above technical solution, the hypromellose is prepared by a method comprising the following steps:
[0019] 1) Add the raw materials and alkali solution into a reaction kettle containing a solvent, stir evenly, and perform alkalization; control the alkalization temperature at 25-35° C. and the alkalization time at 80-140 min; the raw materials are refined cotton and wood pulp cotton;
[0020] 2) Add methyl chloride and propylene oxide into the reactor, stir cold for 10-15 minutes, then heat to 52±2℃, keep warm for 60-90 minutes, then heat to 92±2℃, keep warm for 70-120 minutes;
[0021] 3) adding glacial acetic acid or a mixture of glacial acetic acid and sodium hypochlorite to neutralize the materials in the reactor;
[0022] 4) Discharge the neutralized material into a desolventizing kettle to remove the solvent;
[0023] 5) Wash the material to remove the solvent with hot water at 90-100°C;
[0024] 6) Granulating, drying and crushing the washed material to obtain the hypromellose.
[0025] The hydroxypropyl methylcellulose prepared by the above specific method can further improve the performance of the gypsum-based self-leveling mortar after being modified with the above-mentioned amounts of lithium sulfate and sodium gluconate.
[0026] As a preferred embodiment of the above technical solution, the alkali solution is a sodium hydroxide aqueous solution with a mass concentration of 45-55%.
[0027] As a preferred embodiment of the above technical solution, the raw materials are refined cotton and wood pulp cotton with an average degree of polymerization of 1200 to 1600.
[0028] As a preferred embodiment of the above technical solution, the mass ratio of refined cotton to wood pulp cotton is (2-6):1, and more preferably 4:1.
[0029] As a preferred embodiment of the above technical solution, the mass ratio of each substance is as follows: raw material: alkali solution: methyl chloride: propylene oxide = 1: (0.7-0.9): (0.5-2.0): (0.1-0.4).
[0030] As a preferred embodiment of the above technical solution, in step 4), the amount of glacial acetic acid used is 0.3-0.5% of the total mass of the materials in the reactor, and the amount of sodium hypochlorite used is 0.8-1.2% of the total mass of the materials in the reactor.
[0031] Another object of the present invention is to provide a method for preparing the additive composition.
[0032] A method for preparing a hydroxypropyl methylcellulose modified additive composition specially used for gypsum-based self-leveling mortar comprises weighing hydroxypropyl methylcellulose, lithium sulfate and sodium gluconate according to the above-mentioned mass proportion and mixing them in a dry powder mixer to obtain the hydroxypropyl methylcellulose additive composition.
[0033] As a preferred embodiment of the above technical solution, the hydroxypropyl methylcellulose, lithium sulfate and sodium gluconate are ground and sieved by a pulverizer and a sieving machine before being mixed by a dry powder mixer; or ground and sieved by an integrated pulverizing and sieving machine.
[0034] In summary, the present invention has the following beneficial effects:
[0035] 1. The present invention uses lithium sulfate and sodium gluconate to modify hydroxypropyl methylcellulose, which significantly improves the workability, suspension, stability and strength of the gypsum-based self-leveling mortar after hardening, which is mainly manifested in: good fluidity and convenient construction operation; good suspension, no sedimentation, no stratification after hardening; good stability, no water seepage, and improved surface flatness; experiments also show that the flexural and compressive strengths of the hardened mortar are significantly improved;
[0036] 2. The hydroxypropyl methylcellulose modified additive composition prepared by the method of the present invention has the characteristics of fast dissolution speed, good suspension, uniform and stable viscosity, etc., and is particularly suitable for gypsum-based self-leveling mortar;
[0037] 3. The gypsum-based self-leveling mortar using the hydroxypropyl methylcellulose modified additive composition of the present invention has the advantages of good fluidity, good suspension, good stability, and smooth surface; the product can be automatically leveled under the action of its own weight and slight external force, which greatly improves the construction efficiency and has good retarding effect and stability; the retarding time of the product is increased, so that the gypsum-based self-leveling mortar does not have undesirable phenomena such as segregation, stratification, and water seepage during the coagulation and hardening process; the application of the hydroxypropyl methylcellulose modified additive composition of the present invention also greatly improves the strength of the gypsum-based self-leveling mortar and imparts good wear resistance;
[0038] 4. The preparation process of the present invention is simple and has a high degree of safety;
[0039] 5. The present invention can meet the requirements of new floor decoration materials for high flatness of the ground, has obvious advantages in thick layer self-leveling construction, and is an ideal supporting material for geothermal heating. Moreover, after hardening, the gypsum self-leveling mortar has the advantages of breathing, humidity adjustment, and environmental protection, which can improve the quality of life in housing. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 It is a side view of the flexural test block of Examples 2 to 6;
[0041] Figure 2 It is a side view of the flexural test blocks of comparative examples 1 to 4;
[0042] Figure 3 Surface views of the leveling test blocks of Examples 2 to 6;
[0043] Figure 4 Surface views of the leveling test blocks of Comparative Examples 1 to 4. DETAILED DESCRIPTION
[0044] The present invention is further explained below in conjunction with the accompanying drawings.
[0045] The following specific implementation methods are merely explanations of the present invention, not limitations of the present invention. Any changes made by those skilled in the art after reading the specification of the present invention will be protected by patent law as long as they are within the scope of the claims.
[0046] Example 1. Preparation of Hydroxypropyl Methylcellulose
[0047] A. Alkalization
[0048] Add refined cotton and wood pulp cotton with an average polymerization degree of 1200 to 1600 and a 50% sodium hydroxide aqueous solution into a reactor and stir. The mass ratio of refined cotton to wood pulp cotton is 4:1, the pressure of the reactor is -0.1Mpa, the frequency of the reactor is 30Hz, the current of the motor is 80A, the alkalization time is 90 minutes, and the alkalization temperature is controlled at 30℃.
[0049] B. Etherification
[0050] After the alkalization is completed, the current of the motor is adjusted to about 40A, and the propylene oxide and methyl chloride in the previous premix tank are added into the reactor together. After cold stirring for 10 minutes, the temperature is raised to 52±2°C in the first stage, and then kept warm for 75 minutes. After the second heating to 92±2°C and keeping warm for 90 minutes, the previously prepared inorganic sodium hypochlorite and organic glacial acetic acid are added at the same time and stirred for 15 minutes. The mass ratio of the total material mass of the reactor to the sodium hypochlorite and glacial acetic acid is 1:0.01:0.004.
[0051] C. Granulation and drying
[0052] The reacted materials are discharged into a desolventizing kettle to separate the materials from the solvent, and washed twice with 95°C hot water to remove by-products and sodium ions. Granulation is then performed, followed by drying and crushing with a Czechlin grinder, with a screening rate of more than 98%, to obtain hydroxypropyl methylcellulose.
[0053] In the above steps of this embodiment, the usage ratio of each material is cellulose raw material: alkali solution: methyl chloride: propylene oxide = 1:0.8:1.0:0.2.
[0054] Example 2 Additive composition and gypsum-based self-leveling mortar
[0055] Additive composition:
[0056] 1 kg of hydroxypropyl methylcellulose (Example 1), 0.001 kg of lithium sulfate and 0.003 kg of sodium gluconate were simultaneously put into a dry powder mixer, mixed evenly and set aside.
[0057] Prepare gypsum self-leveling mortar according to the following scheme:
[0058] 900 grams of gypsum, 50 grams of lime, 50 grams of fly ash, 0.8 grams of the additive composition of this example, 2 grams of polycarboxylic acid water reducer, 0.8 grams of defoaming agent, 0.6 grams of protein retarder, and 430 grams of water.
[0059] The obtained self-leveling mortar was tested for 7D compressive and flexural strength according to T / CBMF 82-2020; the stratification state of the side of the flexural test block was observed; and the flatness of the flow surface was observed.
[0060] Example Trihydroxypropyl methylcellulose modified additive composition and gypsum-based self-leveling mortar
[0061] Hydroxypropyl methylcellulose modified additive composition:
[0062] 1 kg of hydroxypropyl methylcellulose (Example 1), 0.0015 kg of lithium sulfate and 0.005 kg of sodium gluconate were simultaneously put into a dry powder mixer, mixed evenly and set aside.
[0063] Prepare gypsum self-leveling mortar according to the following scheme:
[0064] 900 grams of gypsum, 50 grams of lime, 50 grams of fly ash, 0.8 grams of the modified additive composition of hydroxypropyl methylcellulose in this example, 2 grams of polycarboxylic acid water reducer, 0.8 grams of defoaming agent, 0.6 grams of protein retarder, and 430 grams of water.
[0065] The obtained self-leveling mortar was tested for 7D compressive and flexural strength according to T / CBMF 82-2020; the stratification state of the side of the flexural test block was observed; and the flatness of the flow surface was observed.
[0066] Example Tetrahydroxypropyl methylcellulose modified additive composition and gypsum-based self-leveling mortar
[0067] Hydroxypropyl methylcellulose modified additive composition:
[0068] 1 kg of hydroxypropyl methylcellulose (Example 1), 0.001 kg of lithium sulfate and 0.002 kg of sodium gluconate were simultaneously put into a dry powder mixer, mixed evenly and set aside.
[0069] Prepare gypsum self-leveling mortar according to the following scheme:
[0070] 900 grams of gypsum, 50 grams of lime, 50 grams of fly ash, 0.8 grams of the modified additive composition of hydroxypropyl methylcellulose in this example, 2 grams of polycarboxylic acid water reducer, 0.8 grams of defoaming agent, 0.6 grams of protein retarder, and 430 grams of water.
[0071] The obtained self-leveling mortar was tested for 7D compressive and flexural strength according to T / CBMF 82-2020; the stratification state of the side of the flexural test block was observed; and the flatness of the flow surface was observed.
[0072] Example Pentahydroxypropyl methylcellulose modified additive composition and gypsum-based self-leveling mortar
[0073] Hydroxypropyl methylcellulose modified additive composition:
[0074] 1 kg of hydroxypropyl methylcellulose (Example 1), 0.002 kg of lithium sulfate and 0.004 kg of sodium gluconate were simultaneously put into a dry powder mixer, mixed evenly and set aside.
[0075] Prepare gypsum self-leveling mortar according to the following scheme:
[0076] 900 grams of gypsum, 50 grams of lime, 50 grams of fly ash, 0.8 grams of the modified additive composition of hydroxypropyl methylcellulose in this example, 2 grams of polycarboxylic acid water reducer, 0.8 grams of defoaming agent, 0.6 grams of protein retarder, and 430 grams of water.
[0077] The obtained self-leveling mortar was tested for 7D compressive and flexural strength according to T / CBMF 82-2020; the stratification state of the side of the flexural test block was observed; and the flatness of the flow surface was observed.
[0078] Example Hexahydroxypropyl methylcellulose modified additive composition and gypsum-based self-leveling mortar
[0079] Hydroxypropyl methylcellulose modified additive composition:
[0080] 1 kg of hydroxypropyl methylcellulose (Example 1), 0.0015 kg of lithium sulfate and 0.002 kg of sodium gluconate were simultaneously put into a dry powder mixer, mixed evenly and set aside.
[0081] Prepare gypsum self-leveling mortar according to the following scheme:
[0082] 900 grams of gypsum, 50 grams of lime, 50 grams of fly ash, 0.8 grams of the modified additive composition of hydroxypropyl methylcellulose in this example, 2 grams of polycarboxylic acid water reducer, 0.8 grams of defoaming agent, 0.6 grams of protein retarder, and 430 grams of water.
[0083] The obtained self-leveling mortar was tested for 7D compressive and flexural strength according to T / CBMF 82-2020; the stratification state of the side of the flexural test block was observed; and the flatness of the flow surface was observed.
[0084] Comparative Example 1 Gypsum-based self-leveling mortar
[0085] Prepare gypsum self-leveling mortar according to the following scheme:
[0086] 900 g of gypsum, 50 g of lime lime, 50 g of fly ash, 0.8 g of hydroxypropyl methylcellulose of Example 1, 2 g of polycarboxylic acid water reducer, 0.8 g of defoamer, 0.6 g of retarder, and 430 g of water.
[0087] The obtained self-leveling mortar was tested for 7D compressive and flexural strength according to T / CBMF 82-2020; the stratification state of the side of the flexural test block was observed; and the flatness of the flow surface was observed.
[0088] Comparative Example 2 Additive composition and gypsum-based self-leveling mortar
[0089] Additive composition:
[0090] 1 kg of hydroxypropyl methylcellulose (Example 1) and 0.002 kg of lithium sulfate were placed in a dry powder mixer and mixed evenly for later use.
[0091] Prepare gypsum self-leveling mortar according to the following scheme:
[0092] 900 grams of gypsum, 50 grams of lime, 50 grams of fly ash, 0.8 grams of the additive composition of this example, 2 grams of polycarboxylic acid water reducer, 0.8 grams of defoaming agent, 0.6 grams of protein retarder, and 430 grams of water.
[0093] The obtained self-leveling mortar was tested for 7D compressive and flexural strength according to T / CBMF 82-2020; the stratification state of the side of the flexural test block was observed; and the flatness of the flow surface was observed.
[0094] Comparative Example 3 Additive composition and gypsum-based self-leveling mortar
[0095] Additive composition:
[0096] 1 kg of hydroxypropyl methylcellulose (Example 1) and 0.004 kg of sodium gluconate were placed in a dry powder mixer and mixed evenly for later use.
[0097] Prepare gypsum self-leveling mortar according to the following scheme:
[0098] 900 grams of gypsum, 50 grams of lime, 50 grams of fly ash, 0.8 grams of the additive composition of this example, 2 grams of polycarboxylic acid water reducer, 0.8 grams of defoaming agent, 0.6 grams of protein retarder, and 430 grams of water.
[0099] The obtained self-leveling mortar was tested for 7D compressive and flexural strength according to T / CBMF 82-2020; the stratification state of the side of the flexural test block was observed; and the flatness of the flow surface was observed.
[0100] Comparative Example 4 Additive composition and gypsum-based self-leveling mortar
[0101] Additive composition:
[0102] 1 kg of hydroxypropyl methylcellulose (Example 2 of CN 103374075A) was placed into a dry powder mixer together with 0.002 kg of lithium sulfate and 0.004 kg of sodium gluconate, and mixed well for later use.
[0103] Prepare gypsum self-leveling mortar according to the following scheme:
[0104] 900 grams of gypsum, 50 grams of lime, 50 grams of fly ash, 0.8 grams of the additive composition of this example, 2 grams of polycarboxylic acid water reducer, 0.8 grams of defoaming agent, 0.6 grams of protein retarder, and 430 grams of water.
[0105] The obtained self-leveling mortar was tested for 7D flexural and compressive strength with reference to T / CBMF 82-2020; the stratification state of the side of the flexural test block was observed; and the flatness of the flow surface was observed.
[0106]
[0107] From Table 1 we can see that:
[0108] 1. The compressive strength and flexural strength of Examples 2 to 6 are higher than those of Comparative Examples 1 to 3; the compressive strength and flexural strength of Example 5 are the best, indicating that the ratio of the two is preferably 1:2, and the optimal usage of lithium sulfate in hypromellose is about 0.2%.
[0109] 2. In Example 4, the usage of lithium sulfate and sodium gluconate is the least, but the compressive strength and flexural strength are second only to the best example 5, which further illustrates that the best ratio of lithium sulfate to sodium gluconate is about 1:2.
[0110] 3. In Example 3, the total amount of lithium sulfate and sodium gluconate used is the largest, but its compressive strength and flexural strength are relatively low among all the examples, indicating that the ratio of lithium sulfate to sodium gluconate of 3:10 is far from the optimal ratio; despite this, Example 4 still shows better results than the comparative example.
[0111] In summary, the compressive and flexural strengths of Examples 2 to 6 are significantly higher than those of Comparative Examples 1 to 3. This is because under the synergistic effect of sodium gluconate and lithium sulfate, the hydration process of hemihydrate gypsum is controlled more evenly, and the internal crystal structure is arranged evenly, which greatly reduces the internal defects of the gypsum material, thereby significantly improving the structural strength, which is manifested macroscopically as a significant increase in the compressive and flexural strengths.
[0112] It should be noted that all the embodiments and comparative examples showed good fluidity during the test.
[0113] Figure 1 It is a side view of the flexural test block of Examples 2 to 6; Figure 2 It is a side view of the flexural test blocks of comparative examples 1 to 4. Figure 1 In the embodiment, the side surface of the test block has good uniformity and no delamination occurs; Figure 2It can be seen that the test blocks of Comparative Examples 1 and 3 showed obvious stratification, while Comparative Example 2 did not have stratification, but severe bleeding occurred; Comparative Example 4 had no stratification and no bleeding. The main reason for this phenomenon is that lithium sulfate will cover the surface of the mortar particles, and the repulsive force of the charge will increase the distance between the particles, so that they can be better dispersed in the system, thereby greatly improving the suspension of the mortar, solving the stratification of the mortar and improving the overall quality. It can be seen that the hydroxypropyl methylcellulose modified additive composition specially used for gypsum-based self-leveling mortar of the present invention can significantly improve the suspension of gypsum-based self-leveling mortar, so that the self-leveling mortar will not settle or bleed during the hardening process, and will not stratify after hardening.
[0114] Figure 3 Surface views of the leveling test blocks of Examples 2 to 6; Figure 4 Surface views of the leveling test blocks of Comparative Examples 1 to 4. Figure 3 In the embodiment, the test block has no water seepage, and the surface formed after hardening is smooth and flat, which is not only beautiful but also has guaranteed strength. Figure 4 In the comparison examples 1 to 3, there is water bleeding to varying degrees. Due to the surface water bleeding during hardening, the surface after hardening is not smooth enough, and its strength is also affected to a certain extent, and it is easy to produce powder falling. The reason for this phenomenon is Figure 2 It is basically the same as in , it is precisely because of the internal stratification of the mortar that a large amount of material is deposited to the bottom in severe cases, and the mixing water with almost no mortar particles is exposed on the surface, forming a bleeding phenomenon. Although there is no stratification in Comparative Example 2, due to the lack of sodium gluconate, the mortar setting time does not match the optimal hydration time of hemihydrate gypsum, resulting in a large amount of bleeding during hardening, which is particularly obvious in the side view of the anti-bending test block. It can be seen that the hydroxypropyl methylcellulose modified additive composition specially used for gypsum-based self-leveling mortar of the present invention can significantly improve the stability of gypsum-based self-leveling mortar, so that the self-leveling mortar does not bleed during the hardening process, and can improve the surface finish of the self-leveling mortar.
[0115] In summary, the product of the present invention can greatly improve the uniformity of the system after being used for gypsum self-leveling, and the resulting macroscopically observable phenomena are the improvement of compressive and flexural strength; the hardened mortar will not produce stratification; and the hardened mortar surface is smooth and flat. These three aspects of improvement have significant improvement significance for gypsum-based self-leveling mortar, greatly improving its quality.
Claims
1. A hydroxypropyl methylcellulose modified additive composition for gypsum-based self-leveling mortar, characterized in that: It is composed of the following components in parts by weight: Hydroxypropyl methylcellulose 100, Lithium sulfate 0.10~0.15, Sodium gluconate 0.34~0.38; The hypromellose is prepared by a method comprising the following steps: 1) Add the raw materials and alkali solution into a reaction kettle containing a solvent, stir evenly, and perform alkalization; control the alkalization temperature at 25-35°C and the alkalization time at 80-140 minutes; the raw materials are refined cotton and / or wood pulp cotton; 2) Add methyl chloride and propylene oxide into the reactor, stir cold for 10-15 minutes, then heat to 52±2℃, keep warm for 60-90 minutes, then heat to 92±2℃, keep warm for 70-120 minutes; 3) Add glacial acetic acid or a mixture of glacial acetic acid and sodium hypochlorite to neutralize the materials in the reactor; 4) Discharge the neutralized material into the desolventizing kettle to remove the solvent; 5) Wash the material to remove the solvent with hot water at 90~100℃; 6) Granulate, dry and crush the washed material to obtain the hypromellose.
2. The hydroxypropyl methylcellulose modified additive composition for gypsum-based self-leveling mortar according to claim 1, characterized in that: The alkali solution is a sodium hydroxide aqueous solution with a mass concentration of 45-55%.
3. The hydroxypropyl methylcellulose modified additive composition for gypsum-based self-leveling mortar according to claim 1, characterized in that: The raw materials are refined cotton and wood pulp cotton with an average polymerization degree of 1200-1600.
4. The hydroxypropyl methylcellulose modified additive composition for gypsum-based self-leveling mortar according to claim 3, characterized in that: The mass ratio of refined cotton to wood pulp cotton is (2~6):
1.
5. The hydroxypropyl methylcellulose modified additive composition for gypsum-based self-leveling mortar according to claim 1, characterized in that: The mass ratio of each substance is as follows: raw materials: alkali solution: methyl chloride: propylene oxide = 1: (0.7~0.9): (0.5~2.0): (0.1~0.4).
6. The hydroxypropyl methylcellulose modified additive composition for gypsum-based self-leveling mortar according to claim 1, characterized in that: In step 4), the amount of glacial acetic acid used is 0.3-0.5% of the total mass of the materials in the reactor, and the amount of sodium hypochlorite used is 0.8-1.2% of the total mass of the materials in the reactor.
7. A method for preparing the hydroxypropyl methylcellulose modified additive composition for gypsum-based self-leveling mortar according to claim 1, characterized in that: Hydroxypropyl methylcellulose, lithium sulfate and sodium gluconate are weighed according to the mass ratio of claim 1 and mixed in a dry powder mixer to obtain the product.
8. A method for preparing the hydroxypropyl methylcellulose modified additive composition for gypsum-based self-leveling mortar according to claim 7, characterized in that: The hypromellose, lithium sulfate and sodium gluconate are ground and sieved by a pulverizer and a sieving machine before being mixed by a dry powder mixer; or ground and sieved by a pulverizing and sieving machine.
Citation Information
Patent Citations
Method for synthesizing hydroxypropyl methyl cellulose
CN103374075A
High-strength gypsum-based self-leveling mortar and preparation method thereof
CN114835461A
Preparation method of ultra-low-viscosity hydroxypropyl methyl cellulose
CN102816247A
Cement based self-levelling levelling material
CN109231940A